Remote training on updating ENACTS datasets with MALI-METEO - Faniriantsoa, Rija; List, Geneva (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
In many parts of Africa, the primary source of climate data is observation by ground-based weather stations. The main strength of these station observations is that they provide the true measurements of the climate variable of interest. However, in many places, stations are sparse, declining in number, and unevenly distributed. By integrating observations with grided satellite data, ENACTS overcomes issues of data scarcity and poor quality, and introduces quality-assessed, spatially and temporally complete data services into national meteorological agencies. The goal of ENACTS is to provide reliable and readily accessible climate data at high resolution to decision makers. A remote training on updating ENACTS datasets was given to National Meteorological Agency of Mali (L’Agence Nationale de la Météorologie du Mali, MALI-METEO) staff.